(untitled) (Journal of Pharmaceutical Negative Results, 2021)
Using acid digestion (AD), multiple extraction procedure (MEP), toxicity characteristic leaching procedure (TCLP), and equilibrium leach test (ELT), Cd, Cr, Cu, Pb, Ni, and Zn were leached from fresh and partially decomposed municipal solid wastes. By fractionating the heavy metal ions into exchangeable, acid extractable, oxidisable, reducible, and residual fractions, Sequential Extraction (SE) tests were carried out to assess the mobility of the metal ions. The order of the tests' decreasing extraction efficiencies was AD > MEP > TCLP > ELT. Except for Ni, less than 45% of the metal content was in a form that was bioavailable (exchangeable and acid extractable). The levels of total and TCLP extractable metals were within the TCLP regulatory limits and USEPA composting standards, respectively.